Vitamin D supplementation and physical performance in adolescent swimmers - Dubnov-Raz, G.; Livne, N.; Raz, R.; Cohen, A. H.; Constantini, N. W. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
It is hypothesized that vitamin D insufficiency in athletes might negatively affect sport performance. The objective of this study was to examine the effect of vitamin D3 supplementation on physical performance of adolescent swimmers with vitamin D insufficiency. Fifty-three adolescent competitive swimmers with vitamin D insufficiency (serum 25-hydroxyvitamin-D concentrations (25(OH)D)<30ng/ml, mean 24.2 ± 4.8ng/ml) were randomized to receive 2,000IU/day of vitamin D3 or placebo for 12 weeks. Swimming performance at several speeds, arm-grip strength, and one-legged balance, were measured before and after supplementation. The age-adjusted changes in performance variables during the study were compared between groups. 25(OH) D concentrations at study end were significantly higher in the vitamin group compared with the placebo group (29.6 ± 6.5ng/ml vs. 20.3 ± 4.2ng/ml, p < .001), yet only 48% of the vitamin group became vitamin D sufficient with this dosing. No between-group differences were found in the changes of the performance variables tested. No significant differences in performance were found between participants that became vitamin D sufficient, and those who did not. No significant correlation was found between the change in serum 25(OH)D and ageadjusted balance, strength or swimming performance at study end. Vitamin D3 supplementation that raised serum 25(OH)D concentrations by a mean of 9.3ng/ml above placebo in adolescent swimmers with vitamin D insufficiency, did not improve physical performance more than placebo.